The efficacy and potential pharmacological mechanism of Fufang Danshen Tablet in promoting the rehabilitation of ischemic stroke: a meta-analysis and in silico study - Zeng, Xuan; Nie, Yichu; Mo, Jierong; Peng, Zhangwen; Zhou, Tianen; Jiang, Jun (Frontiers in Neurology, 2026)
BackgroundFufang Danshen Tablet (FDT) is a traditional Chinese medicine (TCM) formula with remarkable efficacy in invigorating blood and eliminating blood stasis, thus commonly used in treating ischemic stroke. However, no systemic summary has been conducted to evaluate its efficacy yet. This study aims to determine the efficacy of FDT therapy for promoting the rehabilitation of ischemic stroke and to explore the potential pharmacological mechanism through an in silico approach.MethodsEligible clinical trials involving FDT therapy for ischemic stroke were searched across nine online databases. Meta-analysis was conducted with RevMan and Stata software. Evaluation of the quality of evidence was performed on the GRADE system. Moreover, GEO datasets, network pharmacology, and molecular docking were employed to explore the potential pharmacological mechanism.Results29 clinical trials concerning 1,634 participants were incorporated into the present meta-analysis. Compared with usual care alone, FDT combined with usual care exerted better efficacy in individuals with ischemic stroke, as evidenced by an elevated overall response rate and decreased National Institute of Health Stroke Scale (NIHSS), as well as the improvement of hemorheology, inflammation, and lipid metabolism. Moreover, meta-analysis of FDT individual intervention trials also showed significant therapeutic effects. Further network pharmacology and molecular docking analysis emphasized the potentially important role of the AKT/GSK3β/Cyclin D1 pathway for FDT to regulate oligodendrocyte precursor cells (OPCs) in treating ischemic stroke.ConclusionFDT appears to significantly enhance neurological recovery, promote blood circulation, inhibit the inflammatory cascade, and lower blood lipid levels in patients with ischemic stroke. The AKT/GSK3β/Cyclin D1 pathway was predicted to be a potential mechanism of FDT in intervening ischemic stroke. In the future, more long-term follow-up RCTs with high quality are urgently needed, as well as experimental validations for the pharmacological mechanism.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251015475, CRD420251015475.